The epidemiology of injuries in powerlifting at the London 2012 Paralympic Games: An analysis of 1411 athlete-days - Willick, S. E.; Cushman, D. M.; Blauwet, C. A.; Emery, C.; Webborn, N.; Derman, W.; Schwellnus, M.; Stomphorst, J.; Van de Vliet, P. (Scandinavian Journal of Medicine & Science in Sports, 2016)
Sport injury epidemiology has received increased recognition as a field of sport medicine research that can improve the health and safety of athletes. Injuries among Paralympic powerlifters have not previously been systematically studied. The purpose of this prospective cohort study was to characterize injuries among Paralympic powerlifters. Athletes competing in the sport of powerlifting were followed over the 7-day competition period of the 2012 London Paralympic Games. The main outcome measurements were injury incidence rate (IR; number of injuries per 1000 athlete-days) and injury incidence proportion (IP; injuries per 100 athletes). A total of 38 injuries among 163 powerlifters were documented. The overall IR was 33.3 injuries/1000 athlete-days (95% CI 24.0-42.6) and the overall IP was 23.3 injuries per 100 athletes (95% CI 16.8-29.8). The majority of injuries were chronic overuse injuries (61%). The most commonly injured anatomical region was the shoulder/clavicle (32% of all injuries), followed by the chest (13%) and elbow (13%). The information obtained in this study opens the door for future study into the mechanisms and details of injuries into powerlifters with physical impairments.